Sacred and Profane Dialectics: A Study of Kecak Ramayana Performing Arts at Uluwatu Temple, Bali Indonesia - Hidajat, Robby; Widiati, Utami; Suprihatin, E. W.; Hasyimy, Muhammad ‘Afaf; Jamnongsarn, Surasak (Journal of Urban Culture Research, 2023)
This research focuses on the Ramayana Kecak tourist art in Pecatu Village, South Kuta District, Badung Regency, Bali. The goal is to study the sacred and profane practices in the Ramayana Kecak. In this case the practice of entertainment is accompanied by religious spiritual practices. The method used is a descriptive critical analysis using data from interviews with key informants, observations and a document review. A functional structural theory is used to study the ideas, statements, activities and strategic efforts of the Ramayana Kecak performers. The results are based on the prospective AGIL theory, which explains sacred and profane practices through: (1) Adaptation: Ramayana Kecak is adapted as a main source of livelihood; (2) Goal Attainment: the village community develops the Ramayana Kecak to improve its economy; (3) Integration: the community integrates artistic and spiritual activities; (4) Latency Pattern Maintenance: bonds of kinship, solidarity, and social tolerance are built between artists, the community, and the audience.